Life Re-Decisions – Stories That Divide in Order to Connect - Aleksandra Chmielińska; Monika Modrzejewska-Świgulska (Horyzonty Wychowania, 2025)
RESEARCH OBJECTIVE: The aim of this article is to explore the narrative thread My Own Voice – (Not) My Own Voice, reconstructed through an analysis of the life stories of women who have declared making significant, transformative life changes.